The Relations and Relevances of the Poda Na Lima Batak People's Philosophy with Islamic Views - Siregar, Iskandarsyah; Demidyuk, Lyudmila (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
The essence of a nation's identity, rooted in its traditional values and philosophy, predates its establishment as a sovereign entity. This intrinsic connection to tradition shapes the foundational principles upon which the nation is built. Indonesia, like many other countries, grapples with a multitude of challenges, often encountering complexities and distortions in crafting solutions for each unique circumstance it faces. However, there exists a belief that by drawing upon the philosophical underpinnings and traditional values inherent to its culture, Indonesia can navigate and resolve these issues effectively. Central to this approach is the recognition of the pivotal role that philosophy plays in guiding societal norms and behaviours. In particular, the adoption of religious values, such as those found in Islam, holds significant promise for grounding the populace in the timeless truths encapsulated within traditional customs. Islam, characterized by its universal nature as a religion of